Sleeper shark (Somniosus antarcticus) and other bite wounds observed on southern elephant seals (Mirounga leonina) at Macquarie Island - J Van Den Hoff; MG Morrice (2008)
Sleeper shark (Somniosus antarcticus) and other bite wounds observed on southern elephant seals (Mirounga leonina) at Macquarie Island